Literature Review: The Relationship Between Chronic Energy Deficiency (CED) and The Incidence of Anemia in Pregnant Women - Titi Erina; Atika Zahria Arisanti; Rr. Catur Leny Wulandari1 (Viva Medika, 2025)
Chronic Energy Deficiency (CED) is a condition caused by a lack of energy and protein intake over a long period of time. Globally, the prevalence of CED in pregnant women reaches 35-37%. In Indonesia, the prevalence of CED increased to 17.3% in 2018 compared to previous years. Pregnant women with CED are at risk of various complications, such as anemia, bleeding, abnormal weight gain, and susceptibility to infection. The purpose of this literature review is to determine the relationship between CED and the incidence of anemia in pregnant women. The method used was a literature study by reviewing articles from national and international journals. Searches were conducted through Google Scholar, Semantic Scholar, and PubMed using the keywords: "Anemia in pregnancy, cause of anemia, CED pregnant women, impact of CED, anemia in pregnancy, cause of anemia in pregnant women, chronic energy deficiency in pregnant women" with a time span of 2018-2023. Of the 125 articles found, they were screened based on the inclusion and exclusion criteria, and 12 articles were reviewed. The results showed that there is a significant relationship between CED and increased risk of anemia in pregnant women, where macro and micronutrient deficiencies have a direct impact on hemoglobin production. This review is expected to increase knowledge in the field of midwifery, especially in the prevention and treatment of anemia in pregnant women with Chronic Energy Deficiency (CED), and help health workers provide better services to pregnant women.